If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(5=2x)-8=-12
We move all terms to the left:
-4(5-(2x)-8)=0
We add all the numbers together, and all the variables
-4(-2x-3)=0
We multiply parentheses
8x+12=0
We move all terms containing x to the left, all other terms to the right
8x=-12
x=-12/8
x=-1+1/2
| −243=−9(10+x) | | -15x-188=-2x+137 | | 8x=6=6x+20 | | 12x-46-7x=104 | | 3(x-3)=3x-10 | | 6h+18/2=h+19 | | 10x-127=3x+34 | | 6x50=6x-x50 | | 1/3y+8/3=3y-3 | | 7x-2(x-6)=3(2x-3) | | 2+n/3=3 | | 2y/3-4y/5=1 | | X-1/x-3=x-4/x-5 | | 9=3x+x | | 2/3n+6/1=-9/1 | | 4(z-3)+3z=1+8z | | 8/x-2=14 | | z-12=-43 | | 11x+101x-20=14(8x+13) | | 2y/3-4y=1 | | -3/3/4x-4=28/3 | | r-33=-31 | | 7-0.9x=7 | | -17+15x=14x+20 | | -8.3=w/5+4.5 | | 14d-1/3(6-12d)=124 | | -6=m/3 | | 2x+21=10x-72 | | 3×44-9=x | | -33/4x-4=28/3 | | 7-7p=-2(7+7p) | | 4x+13=-35 |